Could High Mental Demands at Work Offset the Adverse Association Between Social Isolation and Cognitive Functioning? Results of the Population-Based LIFE-Adult-Study. - Rodriguez, F. S.; Schroeter, M. L.; Witte, A. V.; Engel, C.; Loffler, M.; Thiery, J.; Villringer, A.; Luck, T.; Riedel-Heller, S. G. (Am J Geriatr Psychiatry, 2017)
OBJECTIVES: The study investigated whether high mental demands at work, which have shown to promote a good cognitive functioning in old age, could offset the adverse association between social isolation and cognitive functioning. METHODS: Based on data from the population-based LIFE-Adult-Study, the association between cognitive functioning (Verbal Fluency Test, Trail Making Test B) and social isolation (Lubben Social Network Scale) as well as mental demands at work (O*NET database) was analyzed via linear regression analyses adjusted for age, sex, education, and sampling weights. RESULTS: Cognitive functioning was significantly lower in socially isolated individuals and in individuals working in low mental demands jobs-even in old age after retirement and even after taking into account the educational level. An interaction effect suggested stronger effects of mental demands at work in socially isolated than nonisolated individuals. CONCLUSIONS: The findings suggest that working in high mental-demand jobs could offset the adverse association between social isolation and cognitive functioning. Further research should evaluate how interventions that target social isolation and enhance mentally demanding activities promote a good cognitive functioning in old age.
Keywords: Adult; Aged; Aging/*physiology/psychology; Cognitive Dysfunction/*physiopathology; *Employment/psychology; Executive Function/*physiology; Female; Humans; Male; Middle Aged; Neuropsychological Tests/*statistics & numerical data; *Social Isolation; *Social Support